Rumen Bacterial Community Responses to Three DHA Supplements: A Comparative In Vitro Study - Jianmin Zou; Genna Ba; Dian Wang; Mengmeng Li; Shaohong Jin; Chong Chen; Wei Tan; Jian He; Hengsheng Du; Pengjie Wang; Yinhua Zhu (Animals)
The aim of this study was to investigate the loss of docosahexaenoic acid (DHA) from three supplements (two powders and one oil) after digestion (rumen and gastrointestinal) and their effects on the number and composition of rumen bacteria, using an in vitro approach. The concentration of supplements has a significant impact on the DHA loss rate and algal oil exhibited the highest rate of loss, but bioaccessibility was not significantly different from the other supplements. 16S rRNA sequencing showed that three DHA supplements altered the bacterial composition of in vitro batch cultures inoculated with rumen microorganisms from cows, and caused changes in the relative abundance of important bacterial phyla, families, and genera. DHA supplements altered the abundance of bacterial species, including Prevotella, Ruminobacter, Succiniclassicum, Succinivibrio, Lachnospiraceae, and Muribaculaceae. Importantly, these changes may be associated with the ruminal response in biohydrogenation. Algal oil has the most significant impact on rumen microbiota by reducing the richness and diversity of rumen microbiota, and significantly altering the composition of multiple important microbiota.